2023
DOI: 10.1332/175795921x16730110266038
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of participation in a longitudinal survey during the COVID-19 pandemic: the case of a low-infection country

Abstract: A large-scale crisis, such as the COVID-19 pandemic, has the potential to affect non-response in cross-sectional and longitudinal surveys. This study utilises a longitudinal survey, conducted prior to and during the COVID-19 pandemic, to examine the factors associated with participation in longitudinal surveys during the COVID-19 period, and how this has changed from prior to the pandemic. We find that a number of demographic groups are more likely to be non-responders to COVID-19 surveys, despite having compl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 22 publications
2
3
0
Order By: Relevance
“…In contrast, mothers with higher levels of education and income, those with older children, and mothers who worked part-time before the pandemic were more likely to have participated in the 2021 data collection. Although these findings are in line with attrition patterns of other surveys conducted during the pandemic (Biddle et al, 2023), it is important to keep in mind that the remaining participants were likely more affluent and less strained when interpreting our results.…”
Section: Datasupporting
confidence: 83%
See 1 more Smart Citation
“…In contrast, mothers with higher levels of education and income, those with older children, and mothers who worked part-time before the pandemic were more likely to have participated in the 2021 data collection. Although these findings are in line with attrition patterns of other surveys conducted during the pandemic (Biddle et al, 2023), it is important to keep in mind that the remaining participants were likely more affluent and less strained when interpreting our results.…”
Section: Datasupporting
confidence: 83%
“…Third, we are aware of some degree of selectivity in our sample because mothers with a higher SES were more likely to have participated in the 2021 follow-up. Even though this is important to keep in mind, it is largely in line with attrition patterns observed in other surveys conducted during the pandemic (Biddle et al, 2023). Yet in contrast to other studies that were launched during the pandemic and based on convenience samples, our data stem from a representative survey that started in 2019.…”
Section: Limitations and Conclusionsupporting
confidence: 70%
“…Longitudinal surveys have played a key role in generating high quality and rapid evidence throughout the pandemic; however, if there is a high degree of selective attrition, then the evidence from these studies will be less generalisable than that of cross-sectional surveys. Biddle and Sollis (2023) report on factors associated with longitudinal participation in an online probability panel survey in Australia during the COVID-19 period. They find that the use of longitudinal survey weights do not entirely overcome the increased selective attrition and that females (compared to those who identified as males), 18-34-year-olds (compared to 55-64-year-olds) and those that were university educated (compared to no post-school qualification) were more likely to participate in subsequent waves.…”
Section: Longitudinal Surveys In the Time Of A Pandemic (Methodologic...mentioning
confidence: 99%
“…Recent novel methodological work (Biddle & Sollis, 2021), however, has suggested that survey methodologists should consider routinely asking respondents about their subjective experiences of participating in COVID-19 related (or similar) surveys. For example, in the Australian National University's five-wave COVID-19 Impact Monitoring Survey Program, answers to two questions (i.e., the respondent's subject experience as to how distressing the survey was, and how glad they were that they participated) were strong predictors of attrition over time-that is, those experiencing lower levels of distress while completing the survey and higher levels of gladness having completed the survey were more likely to complete subsequent waves (Biddle & Sollis, 2021). Elsewhere, Yu et al (2022) reported that self-report difficulty with the COVID-19 health-related quality of life survey predicted attrition across both follow-up waves spanning the first year of the pandemic.…”
Section: Socio-demographic and Mental Health Characteristics Of Adult...mentioning
confidence: 99%
“…Elsewhere, Yu et al (2022) reported that self-report difficulty with the COVID-19 health-related quality of life survey predicted attrition across both follow-up waves spanning the first year of the pandemic. Biddle and Sollis (2021) propose that this type of information about participants' subjective experience of survey participation is valuable for tailoring study invitation communi- . As per best practice (Besançon et al, 2021), we have been strongly committed to Open Science principles from the outset.…”
Section: Socio-demographic and Mental Health Characteristics Of Adult...mentioning
confidence: 99%